Systematic Development of Sandwich Immunoassays for the Plasma Secretome. Issue 15 (22nd July 2019) - Häussler, Ragna S.; Bendes, Annika; Iglesias, MariaJesus; Sanchez‐Rivera, Laura; Dodig‐Crnković, Tea; Byström, Sanna; Fredolini, Claudia; Birgersson, Elin; Dale, Matilda; Edfors, Fredrik; Fagerberg, Linn; Rockberg, Johan; et al.
Abstract: The plasma proteome offers a clinically useful window into human health. Recent advances from highly multiplexed assays now call for appropriate pipelines to validate individual candidates. Here, a workflow is developed to build dual binder sandwich immunoassays (SIA) and for proteins predicted to be secreted into plasma. Utilizing suspension bead arrays, ≈1800 unique antibody pairs are first screened against 209 proteins with recombinant proteins as well as EDTA plasma. Employing 624 unique antibodies, dilution‐dependent curves in plasma and concentration‐dependent curves of full‐length proteins for 102 (49%) of the targets are obtained. For 22 protein assays, the longitudinal, interindividual, and technical performance is determined in a set of plasma samples collected from 18 healthy subjects every third month over 1 year. Finally, 14 of these assays are compared with with SIAs composed of other binders, proximity extension assays, and affinity‐free targeted mass spectrometry. The workflow provides a multiplexed approach to screen for SIA pairs that suggests using at least three antibodies per target. This design is applicable for a wider range of targets of the plasma proteome, and the assays can be applied for discovery but also to validate emerging candidates derived from other platforms.